2004
DOI: 10.1021/jp049063k
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Radiolysis Studies of the Reactions of Carbonate Radical Anion with Myoglobin and Hemoglobin

Abstract: The reactions of carbonate radical anion [systematic name: trioxidocarbonate(•1-)] with different forms of myoglobin and hemoglobin were studied by pulse radiolysis in N 2 O-saturated 0.25 M sodium bicarbonate solutions at pH 10.0 and room temperature. The reactions of CO 3 •with metMb and metHb involve only amino acid residues of the globin and no oxidation of the iron is observed. The second-order rate constants measured are (4.7 ( 0.3) × 10 7 and (1.9 ( 0.3) × 10 8 M -1 s -1 , for metMb and metHb, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…The substitution of • OH with CO 3 •− could enhance degradation if the latter, although less reactive than • OH, undergoes radical-radical recombination at a lesser extent than the hydroxyl radical. The combination of • OH is known to be 275 times higher than that the reaction of CO 3 •− with itself [10,20,21]. At higher dye concentrations, the slight negative effect of bicarbonate ions on the rate of dye destruction may be due to the much slower formation of carbonate radical.…”
Section: Effect Of Bicarbonate Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution of • OH with CO 3 •− could enhance degradation if the latter, although less reactive than • OH, undergoes radical-radical recombination at a lesser extent than the hydroxyl radical. The combination of • OH is known to be 275 times higher than that the reaction of CO 3 •− with itself [10,20,21]. At higher dye concentrations, the slight negative effect of bicarbonate ions on the rate of dye destruction may be due to the much slower formation of carbonate radical.…”
Section: Effect Of Bicarbonate Concentrationmentioning
confidence: 99%
“…For many years, by analogy to the carbonate and bicarbonate anions, it was assumed that this radical normally exists as the protonated form (HCO 3 • ) in the neutral to basic pH range, but it is now firmly established that no protonation of CO 3 •− (reaction (10)) could be observed in the pH range of 0-10 [8], which leaves CO 3 •− as the only relevant carbonate radical species to be considered in this study and in most aquatic chemistry applications. This radical is a strong one-electron oxidant (1.78 [9] and 1.59 V [10] vs. Normal Hydrogen Electrode (NHE) at pH 7.0 and 12.5, respectively). Carbonate radical may be formed when using ultrasound for water treatment (quenching of hydroxyl radical by HCO 3 − and CO 3 2− ).…”
Section: Introductionmentioning
confidence: 99%
“…•-does not react directly with ferric iron of methemoglobin and metmyoglobin [9,10]. The steady-state radiolysis experiments presented here show that the absorbance in the Soret band (characteristic for the heme protein) of catalase and HRP decreases with the dose, i.e., with an increase of the cumulative concentration of CO 3…”
Section: Discussionmentioning
confidence: 69%
“…•-with Fe(III) forms of these proteins, only the oxidation of amino acids takes place [9]. In our earlier studies, we have shown that peroxidase-like activity of cytochrome c significantly increases after the reaction with radiolytically generated CO 3…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation